Korelasi Pertumbuhan dan Kandungan Karaginan Kappaphycus alvarezii Dan Eucheuma Spinosum Dengan Jarak Penempatan Rakit Apung Yang Berbeda Di Desa Grujugan Kecamatan Gapura Kabupaten Sumenep [Correlation Of Growth And Carragenan Content Of Kappaphycus alvarezii And Eucheuma Spinosum By Different Distance Placement Of Floating Rafts At The Grujugan Village, Sub-District Gapura, Residence Of Sumenep] - Sri Subekti; Lina Wafia Asmi; Moch. Amin Alamsjah (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract The selection of right location is an important succeed factor of the seaweed cultivation to make seaweed a good growth. Seaweed Kappaphycus alvarezii and Eucheuma spinosum contain carrageenan which has been widely used in several industries. The aim of the research is to determine the correlation of growth and carrageenan content K. alvarezii and E. spinosum by different distance placement of floating rafts. Research method using experimental method and experimental design using randomized block design, followed by Duncan's test or Mann Whitney U test and furthermore linear correlation to determine the correlation between growth and carrageenan content. The treatment using different cultivation locations. On K. alvarezii with a distance of 100 m from the beach (RK1), a distance of 400 m from the beach (RK2), and a distance of 700 m from the beach (RK3). E. spinosum at a distance of 100 m from the beach (RE1), a distance of 400 m from the beach (RE2), and the distance of 700 m from the beach (RE3). Each treatment was repeated 9 times. The main parameters observed in this study is the growth rate of once every 10 days, and the content of carrageenan obtained from the extraction of the final harvest. Supporting water quality parameters include: temperature, water transparency, current velocity, substance nutrients (nitrate and phosphate), salinity, and pH. The results showed seaweed K. alvarezii and E. spinosum cultivated at a distance at 400 m from beach has the highest growth rate and yield best carrageenan content. From the results of the calculation of growth and carrageenan content K. alvarezii and E. spinosum with distance floating rafts of different placements had a very strong correlation